Using high performance thin layer chromatography for the detection of pharmacologically active secondary metabolites in Empetrum nigrum L. - A. O. Ponkratova; A. K. Whaley; V. G. Luzhanin; E. V. Zhokhova (Разработка и регистрация лекарственных средств)
Introduction. The article presents the results of the detection of pharmacologically active secondary metabolites in black crowberry Empetrum nigrum L. using the method of high performance thin layer chromatography (HPTLC).Aim. To show the efficiency of HPTLC for conducting preliminary phytochemical analysis to determine the main groups of metabolites in promising medicinal plant species.Materials and methods. HPTLC analysis was carried out on a CAMAG device (Switzerland), using MERCK HPTLC silica gel 60 F154, 20 × 10 cm plates. For the evaporation of the samples, a Heidolph vacuum rotary evaporator (Germany) was used. The aerial parts (shoots) of Empetrum nigrum were harvested next to St. Petersburg State Chemical and Pharmaceutical University (SPCPU) nursery garden of medicinal plants (Leningrad Region, Vsevolozhsky District, Priozerskoe Highway, 38 km) in August 2019.Results and discussion. In the course of the research, four fractions from the aerial parts of Empetrum nigrum were obtained: hexane, dichloromethane, butanol, and water. Then, these fractions were investigated by HPTLC in two solvent systems – n-butanol : acetic acid : water (BAW) (4 : 1 : 2) and hexane : dichloromethane : methanol (HDM) (1 : 2 : 0.5). After scanning densitometric analysis of the plates eluted in the HDM system, it was revealed, that the hexane and dichloromethane fractions have a similar composition and contain the greatest amount of compounds, compared to the butanol and water fractions, and in the BAW system, it was found, that the butanol fraction contains the greatest variety of metabolites. As a result of UV spectroscopy, it was found, that the main groups of compounds contained in the hexane and dichloromethane fractions are derivatives of chalcones, dihydrochalcones, bibenzyls and 9,10-dihydrophenanthrenes. While in the butanol fraction, the main groups of secondary metabolites were derivatives of flavonoids and tanninsConclusion. The data obtained allow us to note the efficiency, speed and simplicity of HPTLC for conducting preliminary phytochemical analysis to determine the main groups of metabolites of promising medicinal plant species.